Um estudo sobre a capacidade de categorização auditiva em função da idade e da presença de dislexia - Brigida Maris Franco Barbosa (2014)
The recognition and identification of sound patterns have a fundamental role in speech perception and in the acquisition of reading and writing. Dyslexia is a neurological disorder that is characterized by difficulty with correct fluency in reading, decoding sounds and spelling. It is believed that the ability of auditory categorization is intrinsically related to speech processing and phonological awareness. The present study aims to analyze the ability of auditory categorization based on age and on the presence of Dyslexia using MorPhala, a speech morphing tool developed at CEFALA-UFMG, to generate auditory stimuli which gradually change from one sound into another well defined sound and to use these stimuli to perform tests. Three groups of subjects were formed: Group 1 (dyslexic aged 7 to 17), Group 2 (no dyslexic aged 7 to 17) and Group 3 (preschoolers aged 3 to 6). The research was divided into 3 stages: (i) a medical interview, meatoscopy and hearing screening, (ii) categorization tests, and (iii) comparison and analysis of the results. Each subject was presented two sets of sentences, with target words which addressed the transition between the sounds /a/ and //, and were forced to point out the picture matching to the word heard. For each pair of figures, there were 17 different stimuli, each one repeated five times for a total of 85 stimuli presented at random. A psychometric categorization curve, modeled by a sigmoid, was plotted for each test. The fixed factors analyzed were the group of individuals, age and gender. 70% of subjects in Group 1 and 71% of Group 3 showed great difficulties in auditory categorization. In Group 2 there was a similar division among the percentage of the individuals with (53%) and without difficulties (47%) in this capacity. Dyslexic subjects have low capacity of auditory categorization in the age group aged 7 to 11 when compared with non-dyslexic. Nevertheless, they acquire such a capacity between 12 and 17 years old. While 60% of non-dyslexic subjects aged 7 to 11 had the ability to categorize, only 18% of dyslexic subjects in the same age group were able to categorize. Later, when aged between 12 and 17, 44% of the dyslexic subjects have ability to categorize, which is comparable to non-dyslexic subjects (46%) of the same age group. In pre-school, the ability of categorization tends to develop progressively, reaching 41% at 6 years. There was no significant difference (p = 0.7) in the ability of auditory categorization between males and females in all 3 groups. The test used in the study contributed to the verification of the development of auditory categorization skill in children and adolescents. It has demonstrated that the ability to categorize speech sounds tends to improve at different speeds depending on age and the presence or not of Dyslexia, being an evidence of the absence of Dyslexia.